Pengembangan E-Booklet Lemea Lebong sebagai Media Pembelajaran Materi Bioteknologi untuk Siswa SMP - Roleka Julia Marcellina; Bhakti Karyadi; Deni Parlindungan; Mellyta Uliyandari; M. Sutarno (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This study aims to develop an e-booklet, namely the Lemea Lebong electronic booklet as a learning medium for biotechnology material. This research method is research and development. Data collection techniques are questionnaires, interview guides and observation. The research instruments were observation sheets, needs analysis questionnaire sheets, teacher interview guides, student readability test questionnaires and expert validation sheets. Data analysis techniques are descriptive and quantitative analysis. The results showed that the Lemea Lebong e-booklet as a learning media for biotechnology materials for students was very feasible to use based on the results of the validation test. Student responses to the readability of the Lemea Lebong e-booklet as a medium for learning biotechnology material for students showed a very good category. In conclusion, the Lemea Lebong e-booklet as a learning medium for biotechnology material is suitable for science learning on biotechnology material. Keywords: E-booklet, Lebong, Lemea